A reflection of the integration of accounting income and economic value added on the decisions of investors - الجنابي, عامر محمد; محمد, ياسر نوري (Journal of Economics and Administrative Sciences, 2014)
The support qualitative information regards as an additional step in the process of decision-making where the method following by companies to provide information help in the creation of value because it is very important to deliver information to investors about their stratigies and what happen truly inside the companies i.e.  every case relating with the expectations of stockhotslder and the prices of markets depending on those expectation ,and if the matter isn’t that there will be lack of confidence thate couldn’t be backed again. The decisions of the investors effected by security ,economic ,political, psychological, emotional ,and financial factors .investores always seek to gain big profits and ,buy and hold stoks by them could gain the highest profits ,and the indicators of the assessment divedided into two main catogarios :the traditional and standard ones depending on the value.The aim of this study is to shed th light on the concept of economic value added as one aspect of optional disclosure and how to rely on the economic value added as an indicator supporting the financial reporting through its integration with traditional accounting income and making a link between them and the related variables helping to rationalize the decisions of investors .this study has been applied in twenty industrial company listed on the Iraq stock exchange (iex)for the year (2010).the hypotheses of the study have been tested by using the statistical analyses ,where the researcher depended on pearson correlation coefficient to test the degree and the type of the relationship and on the simple and multiple regressions analisis resulting in the following result:In 2010 the correlation of EVA with (, ROA, EPS AR, ROE, ROI)is weak postitive . where Eva explaining  R2 when the integration of each of the EVA and NI, 41.2% of ROE, 29.1% ROI, 19.4% ROA, 14.3% EPS, 10% AR.